Depression and type 2 diabetes over the lifespan: a meta-analysis - Mezuk, Briana; Eaton, William W; Albrecht, Sandra; Golden, Sherita Hill (Diabetes care, 2008)
It has been argued that the relationship between depression and diabetes is bi-directional, but this hypothesis has not been explicitly tested. This systematic review examines the bi-directional prospective relationships between depression and type 2 diabetes. A search was conducted using Medline for publications from 1950 through 2007. Reviewers assessed the eligibility of each report by exposure/outcome measurement and study design. Only comparative prospective studies of depression and type 2 diabetes that excluded prevalent cases of depression (for diabetes predicting depression) or diabetes (for depression predicting diabetes) were included. Two sets of pooled risk estimates were calculated using random effects: depression predicting type 2 diabetes and type 2 diabetes predicting depression. Of 42 full-text publications reviewed, 13 met eligibility for depression predicting onset of diabetes, representing 6,916 incident cases. Seven met criteria for diabetes predicting onset of depression, representing 6,414 incident cases. The pooled relative risk (RR) for incident depression associated with baseline diabetes was 1.15 (95% CI 1.02-1.30). The RR for incident diabetes associated with baseline depression was 1.60 (1.37-1.88). Depression is associated with a 60% increased risk of type 2 diabetes. Type 2 diabetes is associated with only modest increased risk of depression. Future research should focus on identifying mechanisms linking these conditions.